PENGUATAN UMKM MELALUI INOVASI “LAPAK UMKM” SEBAGAI UPAYA PEMULIHAN EKONOMI DI MASA PANDEMI - Dimas Arys Prasetyo; Nasikh Nasikh (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The COVID-19 pandemic has changed the global economic order and has had an impact on the Indonesian economy, one of which is the Micro, Small & Medium Enterprises sector. Therefore, innovation is needed as an effort to recover the economy. Madiun City innovated “Lapak UMKM”, a program based on the local economy spread across 27 urban villages in Madiun City. This study has the aim of knowing the development of MSMEs through Lapak UMKM innovations to recover economic recovery due to Covid-19 in Madiun City. This study uses a qualitative method with descriptive analysis. This study uses data obtained directly in the field through observation, documentation and interviews and secondary data obtained through the website of the relevant agency. The research sample was taken using purposive sampling technique. The results of this study indicate that MSMEs continue to be innovative, (1) Lapak UMKM innovations are effective in increasing community empowerment, (2) Lapak UMKM have succeeded in increasing business independence and increasing MSME turnover, (3) Lapak UMKM innovations have succeeded in starting local economy-based businesses, (4) There are still many shortcomings in the implementation of MSME innovation, especially in the field of promotion, and management regulations.